Cost Accounting System and Risk Governance: an Integrated Approach to Risk Management and Cost Efficiency - Yuli Dewi; Muzzayanah Muzzayanah; Surnita Sandi Wiranata (Jurnal Ragam Pengabdian, 2026)
In an increasingly uncertain and complex business environment, organizations are required to achieve operational efficiency while maintaining strategic resilience. Cost Accounting Systems (CAS) provide detailed financial insights that support managerial decision-making, whereas Risk Governance embeds risk awareness into organizational governance structures. Despite their complementary roles, these two domains are frequently implemented in isolation. This study aims to develop an integrative conceptual framework that connects Cost Accounting Systems and Risk Governance to enhance both cost efficiency and enterprise risk management. Using a narrative literature review approach, this article synthesizes academic and professional literature on management accounting, enterprise risk management, and governance. The findings suggest that integrating CAS with Risk Governance improves decision quality, strengthens accountability, and supports sustainable organizational performance by aligning financial information with risk oversight mechanisms. This study contributes to the literature by bridging management accounting and risk governance perspectives and offers a conceptual foundation for future empirical research